Depression Symptoms Among Early Childhood Development Practitioners in South Africa - Kunene, Mercedes Zanele; Mokwena, Kebogile; Mokgatle, Mathildah (Al-Sihah: The Public Health Science Journal, 2024)
The increasing prevalence of depression is a growing global concern, including among early childhood development practitioners. However, there is a dearth of studies on the mental health of these practitioners in South Africa. The objective of this study was to screen for the prevalence and severity of depression symptoms among practitioners. The Patient Health Questionnaire-9 (PHQ-9) and a socio-demographic questionnaire were used to collect data from 402 practitioners. Descriptive analysis of the data was performed using Stata 14. The Pearson chi-square test and logistic regression model were applied to explore associations between socio-demographic variables and PHQ-9 scores and to identify factors significantly associated with depression symptoms. Nearly half of the participants (47.26%) tested positive for depression symptoms across various severity categories, including mild (27.11%), moderate (15.92%), moderately severe (3.48%), and severe (0.75%). Key variables such as the location of the center, the number of children living with the practitioner, substance use, the number of practitioners in the center, the number of children per class, and the total number of children in the center were significantly associated with depression symptoms (p ≤ 0.05). The study recommends the development and implementation of tailored interventions to address the mental health needs of practitioners, thereby improving both the academic and non-academic outcomes of learners.